Studies on Thrombolysis with Streptokinase - Gottlob, R; Blümel, G; Piza, F; Brücke, P; Böhmig, H. J (Thrombosis and Haemostasis, 1968)
1. Human thrombi of various ages obtained by surgery were incubated in SK solution. Whereas thrombi up to 2 days old showed no considerable lysis, older thrombi, in some cases more than 1 month old, showed good lysibility in SK.2. The good lysibility of older thrombi was reproduced in in vitro whole blood clots.3. Similar to the findings obtained in experimental thrombi, we found that in in vitro whole blood clots retraction goes along with a marked decrease in the water content, whereas we find again a moderate rise with increasing age.4. If we add 131I-labelled human serum albumin to the supernatant of in-vitro clots, we see an increased absorption of albumin, particularly in the second and third day after clotting.5. Massive hemolysis sets in on the second and third day in whole blood clots incubated at 37 centigrades in their own serum.6. The following are discussed as possible causes for the improved lysibility of older thrombi and clots : renewed absorption of plasminogen from the milieu ; the release of ferments that may be activated by SK in the process of cytolysis, and a decrease in the content of plasmin inhibitors.7. Based on the findings the suggestion is advanced to attempt lytic therapy with SK even in the case of older clinical thrombi.